2016
DOI: 10.1177/2347631116650550
|View full text |Cite
|
Sign up to set email alerts
|

Success of Student Internship in Engineering Industry

Abstract: Student internship plays a major role in transforming the engineering interns to ready-to-use professionals. Learning at the workplace has become a challenge for the interns due to several issues. A knowledge gap analysis has been depicted considering all stakeholders of the internship, including the intern, faculty, institution and the industrial organization. This article identifies and discusses these issues and provides a framework for effective learning and above-mentioned transformation considering the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Active participation of engineering students in the internship provided a good understanding of learning at the workplace. A student internship played an important role in transforming the engineering graduates to ready-to-use professionals when they joined an organisation after completing their academic work (Prabhu and Kudva, 2016). Raman and Unnikrishnan (2015) suggested that internship as part of the curriculum, if practiced, could uplift the standard of technical education in India, as it helped to bridge the gap between industry and the institute.…”
Section: Involvement Of Engineering Students In Non-classroom Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Active participation of engineering students in the internship provided a good understanding of learning at the workplace. A student internship played an important role in transforming the engineering graduates to ready-to-use professionals when they joined an organisation after completing their academic work (Prabhu and Kudva, 2016). Raman and Unnikrishnan (2015) suggested that internship as part of the curriculum, if practiced, could uplift the standard of technical education in India, as it helped to bridge the gap between industry and the institute.…”
Section: Involvement Of Engineering Students In Non-classroom Activitiesmentioning
confidence: 99%
“…It has been argued that greater interaction between industry and engineering institutions would provide a better understanding of the manpower requirement and institutions could tailor their academic programs accordingly (Banerjee and Muley, 2008). In a recent study, Prabhu and Kudva (2016) have found that an internship programme in industry was essential in transforming engineering graduates to ready-to-use professionals. The study by Sharan (2004) mentioned that there is a need to integrate the courses from humanities and social sciences with engineering curricula to help the engineers' understanding of the societal norms of the workplace.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, faculty participation, as part of a small, highly selective biomedical engineering internship program, was an important factor contributing to the high academic outcomes of the program [22]. In a conceptual paper, Prabhu and Kudva argued for the engagement of faculty in filling the knowledge-application gaps during an engineering internship [50].…”
Section: Theme 3 (Regarding the Academic Institution) Programming Acmentioning
confidence: 99%
“…The benefits of internships are related to a large number of stakeholders. However, specialists emphasise that the main impediments to the success of these programmes are related to the gaps between stakeholders and their insights about internships (Prabhu and Kudva, 2016).…”
Section: Stakeholders' Advantages Of Internship Programmesmentioning
confidence: 99%
“…Therefore, in order to meet their requirements students must understand the business environment and be prepared for certain practical issues, in order to become 'ready-to-use professionals'. It is desired that the throughputs of the universities are in line with the customer requirements (Prabhu and Kudva, 2016). That is why the use of internship programmes and cooperative education schemes increased substantially over the past decades (Beck and Halim, 2008).…”
Section: Introductionmentioning
confidence: 99%